Core Java 9/10 for the impatient (LiveLessons (Indianapolis, Ind.), 2018)
"Core Java 9/10 for the Impatient LiveLessons by Cay S. Horstmann is a concise guide that includes all the latest changes up to Java SE 9 and 10. This training pairs with the recently released second edition of Core Java SE 9 for the Impatient, which has been fully updated to cover Java SE 9 and 10. Horstmann's practical insights and sample code help you quickly take advantage of all that's new, from Java SE 9's long-awaited 'Project Jigsaw' module system to the improvements first introduced in Java SE 8, including lambda expressions and streams."--Resource description page